Inflammation‐Instructed Hierarchical Delivery of IL‐4/miR‐21 Orchestrates Osteoimmune Microenvironment toward the Treatment of Rheumatoid Arthritis. (10th June 2021) - Deng, Yekun; Zhou, Yang; Liang, Qiujun; Ge, Chenglong; Yang, Jiandong; Shan, Bingchen; Liu, Yong; Zhou, Xiaozhong; Yin, Lichen
Abstract: Dysregulated inflammation and failure in resolution account for the incidence and deterioration of rheumatoid arthritis (RA). IL‐4 and miR‐21 possess complementary functions in inhibiting inflammation and fostering resolution. Thus, inflammation‐instructed nanocomplexes (NCs) are herein developed to mediate hierarchical co‐delivery of miR‐21 and IL‐4 to orchestrate the osteoimmune microenvironment against RA. The NCs comprise a cationic inner core assembled from the membrane‐penetrating, helical polypeptide (PG) and miR‐21, an outer layer based on the acid‐responsive, charge reversal polymer (PLL‐CA), and surface‐adsorbed IL‐4. The negatively charged NCs enable prolonged blood circulation after systemic administration, and thus passively accumulate in the inflamed joint. In the slightly acidic microenvironment of inflamed synovium, PLL‐CA transforms from negative to positive, which sheds off to liberate IL‐4 extracellularly and facilitate the intracellular delivery of the PG/miR‐21 core into macrophages. Thus, the anti‐inflammatory miR‐21 cooperates with the proresolving IL‐4 to attenuate inflammation via NF‐κB inhibition, promote macrophage polarization to M2a/M2c phenotypes, propel resolution, and promote tissue repair against Zymosan A‐induced arthritis. This study provides an effective strategy toward the programmed delivery of drug/gene cargoes at different extracellular/intracellular locations, and the combined mechanism of anti‐inflammation and proresolution renders insights into the treatment of inflammatory diseases. Abstract : Inflammation‐instructed nanocomplexes (NCs) are developed to mediate hierarchical co‐delivery of miR‐21 and IL‐4 into inflamed synovium and macrophages in a spatiotemporally controlled manner. The anti‐inflammatory miR‐21 cooperates with the proresolving IL‐4 to attenuate inflammation via NF‐κB inhibition, promote macrophage polarization to M2a/M2c phenotypes, propel resolution, and promote tissue repair against Zymosan A‐induced arthritis.